Surfen‐mediated blockade of extratumoral chondroitin sulfate glycosaminoglycans inhibits glioblastoma invasion. Issue 11 (9th August 2019) - Logun, Meghan T.; Wynens, Kallie E.; Simchick, Gregory; Zhao, Wujun; Mao, Leidong; Zhao, Qun; Mukherjee, Subhas; Brat, Daniel J.; Karumbaiah, Lohitash
Abstract : Invasive spread of glioblastoma (GBM) is linked to changes in chondroitin sulfate (CS) proteoglycan (CSPG)‐associated sulfated glycosaminoglycans (GAGs) that are selectively up‐regulated in the tumor microenvironment (TME). We hypothesized that inhibiting CS‐GAG signaling in the TME would stem GBM invasion. Rat F98 GBM cells demonstrated enhanced preferential cell invasion into oversulfated 3‐dimensional composite of CSA and CS‐E [4‐ and 4, 6‐sulfated CS‐GAG (COMP)] matrices compared with monosulfated (4‐sulfated) and unsulfated hyaluronic acid matrices in microfluidics‐based choice assays, which is likely influenced by differential GAG receptor binding specificities. Both F98 and human patient‐derived glioma stem cells (GSCs) demonstrated a high degree of colocalization of the GSC marker CD133 and CSPGs. The small molecule sulfated GAG antagonist bis‐2‐methyl‐4‐amino‐quinolyl‐6‐carbamide (surfen) reduced invasion and focal adhesions in F98 cells encapsulated in COMP matrices and blocked CD133 and antichondroitin sulfate antibody (CS‐56) detection of respective antigens in F98 cells and human GSCs. Surfen‐treated F98 cells down‐regulated CSPG‐binding receptor transcripts and protein, as well as total and activated ERK and protein kinase B. Lastly, rats induced with frontal lobe tumors and treated with a single intratumoral dose of surfen demonstrated reduced tumor burden and spread compared with untreated controls. These results present a first demonstration of surfen as an inhibitor of sulfated GAG signaling to stem GBM invasion.—Logun, M. T., Wynens, K. E., Simchick, G., Zhao, W., Mao, L., Zhao, Q., Mukherjee, S., Brat, D. J., Karumbaiah, L. Surfen‐mediated blockade of extratumoral chondroitin sulfate glycosaminoglycans inhibits glioblastoma invasion. FASEB J. 33, 11973‐11992 (2019). www.fasebj.org